Writing Difficulties in Dysgraphic Students: A Study Using Word Board Media - Dahlia, Eva; Amriyah , Chairul; Ningrum, Ayu Reza (CV. Tripe Konsultan, 2025)
This study investigates the writing difficulties experienced by students with dysgraphia and evaluates the effectiveness of Word Board media as an instructional intervention. The objective of this research is to identify specific patterns of writing challenges among students with dysgraphia and to assess the impact of a multisensory teaching tool in overcoming those challenges. The study involved 20 students from MI Al-Hidayah and MIS Nurul Asyrof, consisting of 10 students from grade 2 and 10 from grade 3. The participants were selected using purposive sampling based on signs of writing difficulties. A qualitative descriptive approach was employed, using classroom observation, interviews, and document analysis for data collection, while thematic analysis was used to interpret the findings. The results revealed consistent issues such as confusion between visually similar letters (e.g.,